Комплектація цеху лиття металу за моделями, що газифікуються, сучасним 3D-технологічним обладнанням - Шинський, О.Й.; Шалевська, І.А.; Дорошенко, В.C. (Physico-technological Institute of Metals and Alloys, 2024)
A brief overview of typical layouts of Lost Foam Casting (LFС) foundries was made. According to the given examples of shoplayouts, it can be seen that in terms of equipment, the LFS shop based on one-off patterns is no more complex than metalcasting shops based on permanent (wooden or metal) patterns for the production of castings of both complex and simplegeometry. Traditionally, the LFС shop is characterized by a modular composition of equipment and the possibility of variousoptions for the location of some of its sections, in particular, the pattern section and the sand cooling and cleaning (regeneration)section, which can be located outside the main premises of the foundry shop, which contributes to reducing the capitalintensity of production. It is recommended to supplement the plan of the LFС workshop, to determine the locations on the planand to indicate the equipment for 3D printing of patterns. A method of metal casting with gasification in a foundry mold of aprinted pattern with preliminary weight reduction of this pattern by milling its core has been developed. The implementationoption of this method is described on the example of a pattern of a turbine blade. It is proposed to equip the station with thecombined use of a 3D printer and a 3D milling machine for the manufacture of vacuum sand molds according to printed andpartially milled patterns, and it is also shown the schemes of automated stations with 3D printing installations. The LFС processin dry-sand molds from printed patterns is significantly more profitable than QuickCast-type casting from printed patternsfired in kilns from shell ceramic molds. A sketch of the site with the combined use of a 3D printer and a 3D milling machine forthe manufacture of dry sand casting molds based on printed lightweight gasified patterns in such casting molds is shown. Theapplication of 3D technologies will strengthen the value chain of the foundry industry, ensure the competitiveness of foundrymaterials with the adaptation of production methods according to orders, and contribute to the digital intellectualization ofequipment and processes.